2001
DOI: 10.1128/jvi.75.16.7494-7505.2001
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Gray Matter Disease without Demyelination Caused by Theiler's Murine Encephalomyelitis Virus with a Mutation in VP2 Puff B

Abstract: Theiler's murine encephalomyelitis virus (TMEV) is divided into two subgroups based on neurovirulence. During the acute phase, DA virus infects cells in the gray matter of the central nervous system (CNS).Throughout the chronic phase, DA virus infects glial cells in the white matter, causing demyelinating disease. Although GDVII virus also infects neurons in the gray matter, infected mice developed a severe polioencephalomyelitis, and no virus is detected in the white matter or other areas in the CNS in rare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 50 publications
0
67
0
Order By: Relevance
“…This suggests that VP2 puff B of TMEV is important for induction of apoptosis: alteration of VP2 puff B from DA virus (or GDVII-like VP2 puff B) contributes to higher levels of apoptosis. This is of interest since we previously reported that DApB and DApBL2M viruses replicate poorly in the CNS, compared to DA virus (Tsunoda et al, 2001). The negative association between induction of apoptosis and virus growth has been reported in picornavirus infections in vitro (Belov et al, 2003;Lipton, 1996, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that VP2 puff B of TMEV is important for induction of apoptosis: alteration of VP2 puff B from DA virus (or GDVII-like VP2 puff B) contributes to higher levels of apoptosis. This is of interest since we previously reported that DApB and DApBL2M viruses replicate poorly in the CNS, compared to DA virus (Tsunoda et al, 2001). The negative association between induction of apoptosis and virus growth has been reported in picornavirus infections in vitro (Belov et al, 2003;Lipton, 1996, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We enumerated all perivascular cuffs and TUNEL + cells in each representative area, such as the cerebral cortex and thalamus, as well as the total area of five coronal brain sections from five mice per infection, with a light microscope at a magnification of × 100, as described previously (Tsunoda et al, 2001). Correlation of TGF-β1 + cells versus CD3 + T cells or versus vessels that were strongly laminin + was carried out by enumeration of all positive cells in the microscopic field of brain lesions at a magnification of × 400 or × 200, respectively.…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple 4-m-thick tissue sections were cut and mounted onto slides. Viral antigen-positive cells were detected on paraffin sections using TMEV hyperimmune rabbit serum, as previously described (20,22). GFP ϩ cells were detected with rabbit anti-GFP (Abcam, Cambridge, MA).…”
Section: Animalsmentioning
confidence: 99%